Impact of mechanical and thermal cycles at different operating conditions on the ITER toroidal field coil conductor performance. (13th July 2021) - Breschi, M; Cavallucci, L; Tronza, V; Mitchell, N; Bruzzone, P; Sedlak, K
Abstract: The impact of electromagnetic (EM) and thermal cyclic loading (referred as warm-up-cool-down—WUCD) on the Nb3 Sn cable in conduit conductors for the toroidal field magnets of the ITER tokamak should be carefully assessed for the proper operation of the machine. The experience gained during the production phases of the TF conductors revealed that a degradation occurs when thermal and EM cyclic loading is applied at the nominal operating conditions of 10.78 T and 68 kA. Since at the beginning of the tokamak operation the nominal conditions will not be achieved, it is worth investigating to what extent lower EM loads affect the conductor performance, and the threshold of EM load that triggers the WUCD degradation. The aim of this investigation is to identify critical levels which determine the onset of this degradation, both in terms of thermal and EM cycles, and to study the performance of strands from different suppliers. For this assessment, a set of conductor samples were manufactured including all types of strands to be used in the TF coils of the ITER machine. These samples were subjected to a set of EM and thermal cycles representing in a realistic way the actual operation of the conductors in the ITER machine. The tests were performed in the SULTAN facility of the Swiss Plasma Center at working conditions ranging from 5.4 T–34 kA to 10.78 T–68 kA. This work presents the results obtained in these tests in terms of current sharing temperature ( T cs ), effective strain, rate of degradation at different working conditions and their implications for the prospected conductor performance in the machine.